Alphaworld: one step, two step - Woolley, Marilyn (Oxford University Press Melbourne, 2004)
"One Step, Two Step" is a children$1 (Bs picture book that explores the theme of taking small, manageable steps towards achieving goals or overcoming challenges. The story typically follows a character who faces various situations, emphasizing the importance of patience and persistence. Through engaging illustrations and simple text, it encourages young readers to embrace the journey of progress, celebrating the idea that even small actions can lead to significant changes. The book conveys a positive message about growth, resilience, and the value of perseverance in everyday life.s